(untitled) (Bangladesh Journal of Agricultural Research, 2017)
Nineteen inbreds of pumpkin (Cucurbita moschata Duch. Ex Poir.) were evaluated at the experimental farm of Olericulture Division, Horticulture Research Centre, Bangladesh Agricultural Research Institute, Gazipur during the rabi season of 2011-12 to select the promising inbreds for higher fruit yield along with other important characters. Thirteen quantitative and three qualitative characters along with fruit fly infestation and virus incidence were studied. The inbreds differed significantly in most of the quantitative characters. All the qualitative characters (fruit shape, fruit skin colour and flesh colour) showed distinct variation among the inbreds. All the inbreds except PK05, PK16, PK17 and PK18 were attacked with Water Melon Virus 2 (WMV2). Fruits of all the lines were more or less infested by fruit fly. The study revealed that the inbreds differing significantly in most of the parameters offer a good scope of selection of better inbreds for desired traits. The flesh thickness, average fruit weight, fruits per plant ranged from 2.61 to 5.39 cm, 1.41 to 5.78 kg and 2.96 to 7.58 respectively. On the basis of yield and other yield attributes nine inbreds viz., PK01, PK02, PK03, PK06, PK07, PK08, PK09, PK10 and PK16 were found promising. These inbreds will be helpful in breeding program to evolve high yielding varieties of pumpkin with better quality. Bangladesh J. Agril. Res. 42(1): 1-11, March 2017